Early community reactions and acceptance of the Sliding-Scale Community Based Health Insurance Scheme in Ethiopia: Qualitative Findings from the treatment arm - Zewdie Birhanu; Beshea Gelana; Nimona Berhanu; Shabu Abdulbari; Bikiltu Abdissa; Jemal Abafita; Badassa Wolteji Chala; Morankar Sudhakar; Gudeta Abebe; Yamirot Andualem; Haimanot Hailu; Dinka Irena; et al. (PLoS ONE, 2026)
Background Ethiopia’s Community-Based Health Insurance (CBHI) launched in 2011, has significantly improved access to healthcare. However, the program has faced several challenges, including concerns about equity, financial sustainability, and limited resource mobilization stemming from its flat-rate premium contribution system. To address these issues, a new sliding-scale premium scheme—based on households’ socio-economic status—has been piloted in 13 districts across Oromia and Sidama regions in Ethiopia. However, empirical evidence on community responses to sliding-scale CBHI models remains unexplored. Objective To generate early empirical evidence on community responses to Ethiopia’s new sliding-scale CBHI policy (socio-economic-based premium differentiation), focusing on acceptability, perceived concerns, and community perceptions of relevance, appropriateness, affordability, equity and fairness. Methods The study was conducted between March and May 2024 in 13 pilot districts across Oromia and Sidama regions where the sliding-scale CBHI pilot was implemented. Using a qualitative design, data were collected through 10 focus group discussions and 16 key informant interviews with community members, local leaders, and health officials, who were purposely selected to capture diverse perspectives. Discussions explored community acceptance, affordability, and experiences with the new scheme. Transcripts were translated and analyzed thematically using ATLAS.ti 7.5, following open coding and triangulation to identify key themes on barriers, facilitators, and overall community response. Results The study found generally positive community reception of the sliding-scale CBHI scheme, which was widely perceived as acceptable, more equitable, inclusive, and better aligned with households’ economic capacity. However, this acceptance was conditional, as it depended on sustained improvements in service quality, consistent availability of medicines, and transparent management of scheme funds. Moreover, operational challenges were also reported, including household misclassification, perceived favoritism, inconsistent application of eligibility criteria, and inadequate communication of the scheme’s procedures and decisions. While stakeholders viewed the reform as a promising step toward a more equitable and inclusive system, sustaining support will require strengthened trust and consistent service delivery. Conclusion The early implementation of Ethiopia’s Sliding-scale CBHI premium system was generally well received by community members and implementers, who viewed it as fair, contextually appropriate, and aligned with households’ ability to pay. The participatory, asset-based classification process enhanced legitimacy, ownership, and trust. However, operational and ethical challenges such as misclassification, favoritism, inconsistent criteria, and limited communication were reported. Participants highlighted the need for improved transparency, grievance handling mechanisms, and consideration of broader livelihood factors to sustain trust and ensure long-term acceptance and equity in the scheme.